2010
DOI: 10.1080/19415250903319309
|View full text |Cite
|
Sign up to set email alerts
|

What's changed? Issues of impact and evaluation in primary science professional development

Abstract: This article reports on issues arising from the external evaluation of a teacher development project -the Active Learning in Primary Science (ALPS) project -undertaken in eight Bristol (UK) primary schools during 2007. The ALPS project aimed to raise pupil attainment in science by developing participating teachers' skills, knowledge and enthusiasm through a programme of centre-based CPD, classroom workshops, in-school consultancy and visits to a hands-on science centre. The evaluation used a combination of doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Additional research has correlated the use of investigation and reflective practices with the development of teachers' professional consciousness (Jacobs, Assaf, and Lee 2011;Lee 2009;Snoek and Moens 2011;Stanulis and Ames 2009;Trent 2011), the improvement of student outcomes (Crippen et al 2010;Davies 2010) and improvements in the teaching procedure (Langdon 2011;Pedder and Opfer 2011;Strand and Bosco-Ruggiero 2011). The specific investigation and research practices suggested in the above articles included the following: the individual trial and testing of different practices during the teaching procedure; the trial and testing of different practices in collaborative communities of practice with the aim of enhancing the teaching procedure; the regular collection of data on the progress of the children by their teachers in relation to the educational methods and practices that teachers used; the use of portfolios and other reflective tools; and dialogue between the educators on different educational issues based on the data collected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research has correlated the use of investigation and reflective practices with the development of teachers' professional consciousness (Jacobs, Assaf, and Lee 2011;Lee 2009;Snoek and Moens 2011;Stanulis and Ames 2009;Trent 2011), the improvement of student outcomes (Crippen et al 2010;Davies 2010) and improvements in the teaching procedure (Langdon 2011;Pedder and Opfer 2011;Strand and Bosco-Ruggiero 2011). The specific investigation and research practices suggested in the above articles included the following: the individual trial and testing of different practices during the teaching procedure; the trial and testing of different practices in collaborative communities of practice with the aim of enhancing the teaching procedure; the regular collection of data on the progress of the children by their teachers in relation to the educational methods and practices that teachers used; the use of portfolios and other reflective tools; and dialogue between the educators on different educational issues based on the data collected.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Helmer et al (2011) found that the teachers who had regular and substantial contact with teachers' advisors had better students' learning outcomes than their colleagues who did not receive feedback so often or did not use the feedback given. In the study of Davies (2010), consultancy support resulted in the enhancement of participants' subject leadership skills in taking a more proactive role in leading change, including action planning, monitoring science teaching and attainment, planning and leading staff meetings, and analysis of pupil assessment data.…”
Section: Introductionmentioning
confidence: 99%